Implementing and evaluating the UPC to promote capacity building among drug demand reduction practitioners in Nigeria: Lessons learned and future directions - Agwogie, M. O; Bryant, N (Adiktologie, 2021)
BACKGROUND: There has been a growing need to improve the knowledge and skills of addiction practitioners worldwide. The development of the Universal Prevention Curriculum (UPC) is one effort to address these needs. This paper is the first to report findings from the implementation of the Core: Introduction to the Universal Prevention Curriculum. AIMS: The aims of this study were to (1) consider the feasibility of implementing UPC in Nigeria; (2) determine whether the programme was delivered as designed; (3) determine whether training objectives were met; (4) highlight connections between the CoP model and essential components of the implementation process; (5) assess trainer proficiency. METHODS: Instruments included a pre-post knowledge assessment developed by UPC national trainers and a post-training survey adapted from the UPC manual that included several open-ended questions and a trainer proficiency survey. PARTICIPANTS: From March 2019 to March 2020, 202 drug demand reduction practitioners participated in the six-day training conducted in ten cohorts. Participants represented a wide range of disciplinary and professional backgrounds. RESULTS: 194 (96%) of the participants completed both the pre- and post-test survey. The difference in the mean scores demonstrate objective gains in foundational knowledge, statistically significant (p < .001) and the effect size was large (2.038). All participants agreed that the curriculum was implemented as designed, objectives were met, and that the course is relevant to their practice with an average rating of between 4.6 and 4.7 on a maximum scale of 5. All facilitators ranked “proficient” (> 76%). CONCLUSION: The practitioners in this study work in varied professional environments and come from diverse ethnic groups with very different languages and traditions. That they all agreed upon the relevance of the training demonstrates the feasibility of implementing a standardized curriculum on substance use prevention in Nigeria.